Counting conformity: evaluating the units of information in frequency-dependent social learning. (December 2015) - Aplin, Lucy M.; Farine, Damien R.; Morand-Ferron, Julie; Cockburn, Andrew; Thornton, Alex; Sheldon, Ben C.
Highlights: We discuss the two possible learning processes underlying conformist transmission. We present an extended analysis of conformity in a previous study of great tits. This shows that both conformist processes generate similar results and outcomes. We argue that functional equivalence is likely in most natural contexts.